Kim Namjoon Speech at the UN Assembly: A Discourse Analysis - Nisa, Lale Chusnun; Suhendra, Erwin; Abdussamad, Zainudin (Jurnal Ilmu Sosial dan Humaniora, 2023)
This research aims at revealing values, belief and assumptions are found in Kim Namjoon’s speech text on campaigning “Love Yourself” and to know types of figurative language used in the speech. This research used descriptive qualitative method. The instrument used in this research was the speech text transcript and speech video that retrieved from YouTube. Data collection techniques used in this research was library research techniques, thus seeing and recording as the main approach to collect the data. The qualitative data analysis was employed after following stages; analyzing data reduction, data display and verification.